Optimizing iterative equivalent-weight quality control with matrix inversion for real-time GNSS satellite clock estimation - Yue Tan; Pan Li; Wenju Fu; Ertao Liang; Junjun Yuan (Advances in Space Research, 2026)

Causal relationships between alzheimer’s disease genetics and brain connectivity alterations: a multi-modal mendelian randomization study with transcriptomic validation of 191 rs-fMRI and 635 DTI neuroimaging traits - Junjun Ji; Zhifan Li; Abao Xing; Gang Luo; Xiaobing Zhai; Wei Xu; Junrong Li; Tao Tan; Ruihong Jia; Yan Yan; Xianbin Zhang; Long Wang; et al. (Brain Imaging and Behavior, 2026)

Identifying the optimal flow conditions of a fishway with two entrances for endemic fishes at a high-altitude hydropower station in the Tibetan Himalaya, China - Sicheng Zeng; Junjun Tan; Junjian Sun; Yuanyang Wang; Giri Raj Kattel; Xiaotao Shi (Ecological Engineering, 2025)

A multiple‐behaviors virtual fish model for simulating fish trajectory in vertical slot fishways - Xiaolong Chen; Xiaotao Shi; Xingyong Deng; Majid Rasta; Junjun Tan; Yu Wang; Yongqiang Jiang; Yanqin Bai (Journal of Fish Biology, 2025)
Fishways are essential for restoring river connectivity and facilitating fish migration, necessitating ongoing research for efficiency optimization. This study developed a fish behavior model to optimize fishway efficiency cost‐effectively. The model simulates swimming trajectories of Schizothorax wangchiachii within a vertical slot fishway incorporating upstream behavior, random behavior, obstacle avoidance, and swimming speed variations. The simulated trajectory exhibits a high consistency with 20 real trajectories, achieving a trajectory overlap rate of 86.7%. This result highlights the model's ability to accurately simulate fish movements, demonstrating its significant potential to revolutionize fishway design.

Distribution characteristics, source analysis and ecological risk assessment of PAHs in tea garden soil in China - Jinzhi Li; Jiantao Xue; Yan Tan; Mingmin Jia; Junjun Feng; Xueqing Feng; Ningguo Zheng; Haoxin Fan; Huaiying Yao (Environmental Research, 2025)

Redefining limits: Impact of nozzle diameter on film flow and atomization beyond the synchronizing radius - Yu Tan; Xudong Chen; Maojiang Jia; Bin Ding; Junjun Wu; Yuelin Qin (Chemical Engineering Journal, 2025)

Multidimensional effects of arable soil organic carbon distribution: a comparison among terrains - Huarong Tan; Fengman Fang; Yuesheng Lin; Junjun Zhi; Youru Yao; Yangbing Liu; Wangbing Liu; Lei Jin; Jin Wang (Journal of Soils and Sediments, 2025)

Molecular insights into the binding mechanism of strontium and cesium on phyllosilicates with different expandability - Junjun Hou; Xiaolan Zhao; Qi Tan; Peng Wang; Xinyi Shi; Qiaohui Fan; Duoqiang Pan; Wangsuo Wu (Science of The Total Environment, 2024)

Fish community dynamics following the low-head dam removal and newly installed fish passage in a headstream tributary of Jinsha River, Southwest China - Junjun Tan; Junjian Sun; Yuanyang Wang; Huiwu Tian; Bixin Cheng; Jie Qing; Xin Yan; Gan Sun; Senfan Ke; Giri Raj Kattel; Xiaotao Shi (Science of The Total Environment, 2024)

Enhanced remediation of real agricultural runoff in surface-flow constructed wetlands by coupling composite substrate-packed bio-balls, submerged plants and functional bacteria: Performance and mechanisms - Shengjiong Deng; Deshou Cun; Rufeng Lin; Dongliang Peng; Yanduo Du; Aoxue Wang; Bowen Guan; Rong Tan; Junjun Chang (Environmental Research, 2024)

A review of cleaner production of glass-ceramics prepared from MSWI fly ash - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Junjun Wu; Bin Ding (Journal of Environmental Management, 2024)

Evaluation of pool-and-weir fishway efficiency for the upstream spawning migration of Qinghai Lake's naked carp - Senfan Ke; Elsa Goerig; Kaiwen Pang; Huaiyao Ji; Dongqing Li; Jiawei Xu; Junjun Tan; Hongfang Qi; Xiaotao Shi (Ecological Engineering, 2024)

Diversity and influencing factors of microbial communities in rhizosphere and nonrhizosphere soils of tea plant - Junjun Feng; Mingmin Jia; Yan Tan; Hongwen Yue; Xueqing Feng; Ningguo Zheng; Juan Wang; Jiantao Xue (Journal of Soils and Sediments, 2024)

Application of microbially induced calcium carbonate precipitation (MICP) process in concrete self-healing and environmental restoration to facilitate carbon neutrality: a critical review - Junjun Chang; Dongyang Yang; Cheng Lu; Zhitao Shu; Shengjiong Deng; Liwei Tan; Shaoqing Wen; Ke Huang; Pengchang Duan (Environmental Science and Pollution Research, 2024)

Enhancing sustainable valorization: Harmless synergistic melting treatment for high-value vitreous products from MSWI fly ash and electrolytic manganese residue - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Bin Ding; Junjun Wu (Waste Management, 2023)

Uncovering the origin of surface-redox pseudocapacitance of molybdenum phosphides enables high-performance flexible sodium-ion capacitors - Yalong Jiang; Runya Han; Jun Dong; Ruohan Yu; Shuangshuang Tan; Fangyu Xiong; Qiulong Wei; Junjun Wang; Lianmeng Cui; Haiyang Tian; Yingkui Yang; Qinyou An (Chemical Engineering Journal, 2023)

Covalent-crosslinking IRMOF-3-NH2/PVC ultrafiltration membrane for simultaneous removal of bisphenol A and Cd2+ ions in water - Yong Pan; Wei Huang; Yong Zhou; Feng Liu; Chen Zhu; HaiXia Pang; JunJun Tan; BaoMing Xu (Journal of Cleaner Production, 2023)

Inversion of TEM measurement data via a quantum particle swarm optimization algorithm with the elite opposition-based learning strategy - Junjun Jiao; Jiulong Cheng; Yuben Liu; Haiyan Yang; Dingrui Tan; Peng Cheng; Yuqi Zhang; Chenglin Jiang; Zhi Chen (Computers & Geosciences, 2023)

Swimming behaviour of silver carp ( Hypophthalmichthys molitrix ) in response to turbulent flow induced by a D ‐cylinder - Senfan Ke; Zhiying Tu; Elsa Goerig; Junjun Tan; Bixin Cheng; Zhimin Li; Xiaotao Shi (Journal of Fish Biology, 2022)
Turbulence is a complex hydraulic phenomenon which commonly occurs in natural streams and fishways. Riverine fish are subjected to heterogeneous flow velocities and turbulence, which may affect their movements and ability to pass the fishways. However, studies focusing on fish response to turbulent flows are lacking for many species. Here we investigate the effects of the turbulence created by a vertical half‐cylinder of various diameters (1.9, 2.5, 3.2 and 5.0 cm) on the swimming ability and behaviour of silver carp, Hypophthalmichthys molitrix . The large D‐cylinders (3.0 and 5.0 cm) create specific vorticity and reduced velocities areas in their vicinity, which favours flow refuging behaviours (FRBs) and thus increased relative critical swimming speeds ( U rcrit , BL/s) of silver carp, by comparison to free‐flow conditions and cylinders of smaller diameter (1.9 and 2.5 cm). The flow speed at which silver carp maximized FRBs such as Karman gaiting downstream of the cylinder, holding position in the bow wake or entraining on the side ranged from 40 to 70 cm s −1 , depending on fish body size. When holding station near a cylinder under optimal flow speeds, the distance between the fish and the cylinder is related to the size of the fish, but also to the size of the cylinder and the produced vortices. The optimal holding region in the drag wake of the cylinder ranged from 28 to 40 cm downstream of the centre of the cylinder, depending on the size of the fish. Smaller fish, however, tend to use the reduced velocities areas located in the bow wake of the large cylinders. We hypothesize that fish will display FRBs, including maintaining a Karman gait in turbulent flow, when the ratio of the cylinder diameter to their body length is between 1:3 and 1:4. They also match their tail beat frequency to the vortex shedding frequency of the cylinder. Our results provide a better understanding of how silver carp respond to turbulent flows around physical structures, with implications for the design of nature‐like fishways or exclusion devices in both its native and invasive ranges.

An improved method used for evaluating potential environmental pollution risk based on spatial distribution and density of farms - Jianghui Wen; Bianyu Zhen; Zhenyu Pu; Xia Peng; Junjun Tan; Zhongbao Shao; Bosheng Bao; Zhiping Ran; Qishuang Gao; Bing Deng (Environmental Science and Pollution Research, 2021)

Mechanisms Underlying the Regulation of Root Formation in Malus hupehensis Stem Cuttings by Using Exogenous Hormones - Wangxiang Zhang; Junjun Fan; Qianqian Tan; Mingming Zhao; Fuliang Cao (Journal of Plant Growth Regulation, 2017)

Histone acetylation and reactive oxygen species are involved in the preprophase arrest induced by sodium butyrate in maize roots - Qi Zhang; Pu Wang; Haoli Hou; Hao Zhang; Junjun Tan; Yan Huang; Yingnan Li; Jinping Wu; Zhengming Qiu; Lijia Li (Protoplasma, 2017)

Exogenous EDDS modifies copper-induced various toxic responses in rice - Junjun Tan; Shibin He; Shihan Yan; Yingnan Li; Hui Li; Hao Zhang; Lin Zhao; Lijia Li (Protoplasma, 2014)